Formation of highly charged quasi-molecular ions of a polycationic [60]fullerene hexakis-adduct and their fragmentation behavior in the gas phase - Li, Jing; Nye, Leanne C.; Wasserthal, Lennard; Vinh, Chau; Kirschbaum, Rolf; Ivanovic-Burmazovic, Ivana; Hirsch, Andreas; Drewello, Thomas (European Journal of Organic Chemistry, 2015)
A novel polycationic [60]fullerene hexakis-adduct has been synthesized and investigated by electrospray ionization and tandem mass spectrometry. The polycationic ligand system comprises 12 pre-formed positive charges, compensated in the neutral molecule by bromide anions. Stable quasi-molecular cations were obtained through the release of the anionic counter ions covering a charge-state envelope from 3+ to 12+. Collision-induced dissociation experiments revealed three fragmentation pathways. A dominant neutral loss channel leads to daughter ions of the same charge state as the highly charged precursor ion and singly charged daughter ions can be expelled from the polycations through two distinct dissociation channels involving both the neutral and the charge-carrying part of their ligands.
Keywords: Electrospray ionization; Fullerenes; Mass spectrometry; Polycations

Laser Desorption Mass Spectrometry of End Group-Protected Linear Polyynes: Evidence of Laser-Induced Cross-Linking - Kirschbaum, Rolf; Prenzel, Dominik; Frankenberger, Stephanie; Tykwinski, Rik; Drewello, Thomas (Journal of Physical Chemistry C, 2015)
End group-protected linear polyynes of composition Tr*-(C C)(n)-Tr* (with Tr* representing the super trityl group and n = 2, 4, 6, 8, 10) and tBu-(C C)(6)-tBu (with tBu being the tertiary butyl group) have been studied by laser desorption ionization (LDI) time-of-flight (ToF) mass spectrometry. tBu-terminated polyyne molecules show considerably higher stability during laser activation than Tr*-end-capped polyyne molecules. A key feature is the abundant formation of oligomeric species upon laser activation. Tandem mass spectrometry reveals strong bonding within the oligomers which indicates cross-linking of the former polyynes within the oligomers. The process is more abundantly occurring and less energy demanding than the laser-induced coalescence of C-60. Cross-linking is more efficient with the smaller end group (tBu), and larger oligomers are formed when the chain length of the polyyne increases, both a result of enhanced interaction of the triple bonds in neighboring chains. The presence of the matrix molecules in matrix-assisted (MA)LDI hinders the polyyne interaction, and oligomer formation is markedly reduced.

Synthesis and aggregation properties of polycationic perylenetetracarboxylic acid diimides - Schönamsgruber, Jörg; Schade, Boris; Kirschbaum, Rolf; Li, Jing; Bauer, Walter; Boettcher, Christoph; Drewello, Thomas; Hirsch, Andreas (European Journal of Organic Chemistry, 2012)
The synthesis and structural characterization of a first family of dendronized polycationic perylenetetracarboxylic acid diimides (PDIs) 7, 8, and 10 is reported. They were obtained by amide coupling reactions of pyridinium salt head groups with terminal carboxylic groups of Newkome-dendron-type functionalized PDIs. Resulting pyridinium-terminated PDIs 7, 8, and 10 are highly water-soluble, independent of the pH value. This is due to 6, 18, and 9 permanent positive charges, respectively. PDIs 7 containing the smaller first-generation dendrons exhibit a pronounced aggregation behavior in water. This was studied by absorption and fluorescence spectroscopy, by pulsed-gradient spin-echo (PGSE, DOSY) NMR measurements, and by cryo-transmission electron microscopy (cryo-TEM). The counterparts containing the bulkier second-generation dendrons hamper aggregation, and as a consequence intermolecular π-π stacking interactions between the perylene cores is suppressed. © 2012 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.